Effects of Beta vulgaris powder on growth and survival of common carp Cyprinus carpio - Amiri, Nahid; Aberoumand, Ali; Nejad, Saeed Ziaee (Journal of Fisheries, 2019)
The use of plant material in a diet to increase the growth of fish may be beneficial and can reduce the production cost. This research was carried out at Behbahan University, Iran, in 2016 with a view to determining effects of Beta vulgaris powder on feeding, growth and survival of common carp (Cyprinus carpio). A total of 360 individuals (mean weight, 20 g; mean standard length, 9 cm) were randomly divided into 12 tanks for treatments. Fish were fed diets with 0% (control), 0.5% (T1), 1% (T2) and 2% (T3) of B. vulgaris powder for six weeks. The results showed that the addition of B. vulgaris to fish diets had a positive effect on survival index and feed conversion index of fish. The presence of B. vulgaris in the diet had increased specific growth rate, and hepatosomatic and viscerosomatic indices.